Royal College of Art Photography 2008. - Burgin, Victor; Lomax, Yve; Richon, Olivier; Santos, Luisa (London : Royal College of Art London, 2008)
Becker, Benjamin ; Camilleri, Oana ; Caruana, Natasha ; de Vries, Caroline ; Hamill, Leonora ; Haywood, Thomas ; Layton, Jessica ; Levy, Alastair ; Longhurst, Jo ; Ludwig, Susanne ; Matar, Diana ; Paredaens, Roel ; Pasquier, Edith Marie ; Pinsker, Patricia ; Pustola, Konrad ; Ronacher, Anja ; Sear, Hal ; Sonzogni, Annalisa ; Tiller, Jamie ; Woolley, Dawn
biog. p. 183
Engels
Exhibition. Royal College of Art Photography 2008. London. Royal College of Art London. 19.09.2008 - 14.12.2008
boek